Investigation of the immune-modulatory effects of erythromycin - Fernandes, Antonio, Celestino (My University, 1986)
The Literature Review covers the immunosuppressive and immunopotentiating properties of antibiotics on the immune system and the effects these could have on the resolution of an infection. The possible pathogenic mechanisms of C. albicans are also reviewed in this section. The experimental section shows that pre-treatment of mice with erythromycin increases the mean survival time following intraperitoneal inoculation of C. albicans. It was shown that erythromycin enhanced lymphocyte transformation and PMNL migration in both in-vivo and in-vitro situations. These enhanced immunological components probably caused improved survival times in the aforementioned animal experiments. To investigate the effects of oral administration of erythromycin on in-vivo PMNL migration in adult volunteers a new quantitative test which could only be applied to humans was developed and is described in detail. Using this method preliminary data were obtained which show that erythromycin increases PMNL migration in-vivo.
A Dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, for the Degree of Master of Science (MED). JOHANNESBURG, 1986
Keywords: Erythromycin; In Vitro Techniques; Neutrophils